Does implementation of and adherence to enhanced recovery after surgery improve perioperative nutritional management in colorectal cancer surgery?. Issue 6 (18th March 2022) - Besson, Alex J.; Kei, Christy; Djordjevic, Aleksandra; Carter, Vanessa; Deftereos, Irene; Yeung, Justin
Abstract: Background: Malnutrition is independently associated with poor outcomes in colorectal cancer (CRC) surgery including increased complications and length of stay (LOS). The purpose of this study was to identify changes to perioperative nutritional management and surgical outcomes post implementation of an enhanced recovery after surgery (ERAS) protocol. Methods: Data on LOS and adherence to the ERAS protocol, including preoperative fasting time, nutritional assessment and supplementation was prospectively collected for the pre‐ERAS group who underwent surgery for CRC between February and August 2019. The post‐ERAS group involved a retrospective analysis of prospectively collected data of patients who underwent surgery between October 2019 and July 2020. Results: One hundred and thirty patients were included, (Pre‐ERAS n = 42, Post‐ERAS n = 88). A reduction in time to first solid intake by 1 day ( P = 0.010), time to first bowel action ( P = 0.007) and incidence of nausea ( P < 0.001) was seen in the post‐ERAS group. Provision of postoperative oral supplements increased from 33.3% to 70.5% ( P < 0.001) in the post‐ERAS group. Thirteen post‐ERAS patients had a ≥ 70% adherence to the ERAS protocol and this subgroup had an associated reduction in LOS, 6.5 (4) days to 5 (3), P = 0.020. Conclusion: Implementation of the ERAS protocol improved perioperative patient care and outcomes. Early feeding was associated with reduced gastrointestinal symptoms without an increase in complications. Adherence to ERAS was associated with a reduction in LOS. Further research is required to evaluate the role of preoperative nutritional screening and intervention within an ERAS protocol. Abstract : Clinical characteristics of the cohort pre‐ERAS and post‐ERAS implementation.